STRATEGI PEMASARAN PRODUK PEMBIAYAAN MURABAHAH DALAM PENINGKATAN DANA RITEL KONSUMER (Studi pada KSPPS Karya Mandiri Jerowaru) - Intan Oktaviani; Sanurdi Sanurdi; Dahlia Bonang (Universitas Islam Negeri Mataram, 2022)
The purpose of this study is to find out how the strategy and effectiveness of the implementation of marketing of murabahah financing products carried out by KSPPS Karya Mandiri Jerowaru. The research method used is qualitative, with data collection techniques, namely observation techniques, interviews and documentation. The subject of this study was the chairman of the board and field employees of KSPPS Karya Mandiri. The results of this study show that the marketing strategy of murabahah financing products is to use a marketing mix and is quite effective.